Electron and ion spectroscopy of the cyclo-alanine–alanine dipeptide. Issue 10 (24th February 2022) - Chiarinelli, Jacopo; Barreiro-Lage, Darío; Bolognesi, Paola; Richter, Robert; Zettergren, Henning; Stockett, Mark H.; Díaz-Tendero, Sergio; Avaldi, Lorenzo
Abstract : The VUV photoionisation and photofragmentation of cyclo-alanine-alanine (cAA) has been studied in a joint experimental and theoretical work. The photoelectron spectrum and the photoelectronphotoion coincidence (PEPICO) measurements, which enable control of the energy being deposited, combined with quantum chemistry calculations, provide direct insight into the cAA molecular stability after photoionisation. The analysis of the ion-neutral coincidence experiments with the molecular dynamics simulations and the exploration of the potential energy surface allows a complete identification of the fragmentation pathways. It has been found that the fragmentation always start with the ring opening through the C–C bond cleavage, followed by release of neutral moieties CO or HNCO. Abstract : The VUV photoionisation and photofragmentation of cyclo-alanine–alanine (cAA) has been studied in a joint experimental and theoretical work. The photoelectron spectrum and the photoelectron–photoion coincidence (PEPICO) measurements, which enable control of the energy being deposited, combined with quantum chemistry calculations, provide direct insight into the cAA molecular stability after photoionisation. The analysis of the ion-neutral coincidence experiments with the molecular dynamics simulations and the exploration of the potential energy surface allows a complete identification of the fragmentation pathways. It has been found that the fragmentation always starts with the ring opening through the C–C bond cleavage, followed by release of neutral CO or HNCO moieties.